Scenario-based evaluation of integrated urban water management framework: a decision making approach - Maurya S.P.; Ohri A.; Singh P.K.; Singh R. (My University, 2025)
In general, urban water management has been viewed as an exercise of meeting the domestic and industrial water demands from surface water and ground water sources. Nevertheless water-based development planning requires realistic estimation of balance between supply and demand within the geographical boundary. Recently, water management system is facing challenges of sustainable development goals (SDGs) in urban water sector. In the present paper an attempt has been made to review the various frameworks and systems developed for evaluating sustainability of an integrated urban water management (IUWM). Further, a computer application-based conceptual framework has been developed as a decision support system for integrated urban water management (DSS_IUWM) taking urban water management of Varanasi City (UP, India) as a case study. With the combination of available alternate water supply in the city, a scenario-based urban water balance has been evaluated. The study indicates that urban water balance (UWB) of Varanasi City is under unsustainable water condition with a negative value of 97 MCM. The study finally reports that a water sustainable condition in Varanasi City may be achieved through augmentation of storm water (55.4 MCM) management or reduction in fresh water demand through reuse of reclaimed water (36.5 MCM). Copyright © 2023 Inderscience Enterprises Ltd.